FORMULATION AND EVALUATION OF VENLAFAXINE HYDROCHLORIDE SUSTAINED RELEASE MATRIX TABLET - Pg, Mahesh; S, JEGANATH (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim: The term modified-release drug product is used to describe products that alter the timing and/or the rate of release of the drug substance. Objective: The objective of the present study was to formulate and evaluate the sustained release matrix tablet of venlafaxine hydrochloride. Methods: Venlafaxine hydrochloride is a structurally novel antidepressant for oral administration. It is widely prescribed for the treatment of depression, generalized anxiety disorder, and social anxiety disorder. Venlafaxine hydrochloride is currently available as immediate release tablet and as an extended release capsules under the brand names of Effexor (WYETH AYERST) and Effexor XR (WYETH AYERST). The biological half-life of venlafaxine very short (5 h) and the dose is to be taken 2–3 times a day and the recommended maximum daily dose is 75–450 mg/day. Venlafaxine hydrochloride is an antidepressant and so it is to be taken for quite a long period. Hence, to reduce the dosing frequency, simple, lower cost sustained release tablets of venlafaxine were preferred for the development. Conclusion: The venlafaxine hydrochloride sustained release matrix tablets shown controlled release profile as per the release profile of the innovator is EffexorTm_XR. The sustained release of this matrix tablet reduces the dosing frequency and reduces the side effects, by which in a long-term therapy, it may be useful as a product with patient compliance for the treatment of major depression disorder.